2022
DOI: 10.3174/ajnr.a7431
|View full text |Cite
|
Sign up to set email alerts
|

ADC for Differentiation between Posttreatment Changes and Recurrence in Head and Neck Cancer: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Previous studies reported that the ADC values of recurrent head and neck cancer lesions are lower than those of posttreatment changes, however, the utility of ADC to differentiate them has not been definitively summarized and established. PURPOSE:Our aim was to evaluate the diagnostic benefit of ADC calculated from diffusion-weighted imaging in differentiating recurrent lesions from posttreatment changes in head and neck cancer.DATA SOURCES: MEDLINE, Scopus, and EMBASE data bases were searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that ADC values in recurrent head and neck cancer lesions are lower than those after benign posttreatment changes, [18][19][20] consistent with the results in the present study. The use of normalized ADCs in the present study and the aforementioned normalized DCE-MR imaging parameters is expected to be reproducible in other institutions by minimizing the effects of several factors that may affect the ADC values such as differences in MR imaging scanners, magnetic field strength, and patient variability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that ADC values in recurrent head and neck cancer lesions are lower than those after benign posttreatment changes, [18][19][20] consistent with the results in the present study. The use of normalized ADCs in the present study and the aforementioned normalized DCE-MR imaging parameters is expected to be reproducible in other institutions by minimizing the effects of several factors that may affect the ADC values such as differences in MR imaging scanners, magnetic field strength, and patient variability.…”
Section: Discussionsupporting
confidence: 93%
“…DWI parameters, especially ADC, were lower in the recurrence of head and neck cancers than in benign changes after treatment. [18][19][20] To date, there have been no studies that have investigated the differentiation between head and neck cancer recurrences and posttreatment changes using normalized DWI-ADC that also consider intervendor and interinstitutional reproducibility as in the previously described normalized DCE-MR imaging parameters.…”
mentioning
confidence: 99%
“…The ADC values of sinonasal benign tumors, including STA, have been reported to be higher than those of sinonasal malignant tumors, 59 and in a previous systematic review, the mean maximum ADC of malignant lesions of the head and neck region was reported to be 1.35-1.20 × 10 −3 mm 2 /second. 60,61 The lowest mean ADC value for STA in the present study was 1.5 (10 −3 mm 2 /second); therefore, a relatively high ADC value of at least 1.5 × 10 −3 mm 2 /second or higher in clinically suspected STA may indicate a high probability of STA.…”
Section: Discussionmentioning
confidence: 50%
“…Head and neck malignant tumors have been shown to have lower ADC values than benign lesions (7,8). Although both head and neck cancers and lymphomas are highly cellular tumors, previous studies have shown that lymphomas tend to have particularly low ADC values (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%